Exploring food environments from adolescents’ perspectives in Ethiopia: An overview video - Gebremeskel, Mestawet; Ekesa-onyango, Beatrice; Nabuuma, Deborah Sandra; Tefera, Nahom; Jordan Müller, Irmgard; Termote, Celine (2024)
This video provides a brief overview of our research on adolescents' food environments in Ethiopia, offering a glimpse into the participatory videos created by the adolescents themselves. The video showcases select excerpts, illustrating the diversity of food environments and the types of food options available to adolescents. Full versions of the participatory videos are currently being used to support a co-design process at community level to explore ways to improve the adolescents' food environments.